Epitaxially grown field-activated electroactive polymers for high performance organic electronics. (2013) - Park, Youn Jung; Bae, Insung; Kim, Richard Hahnkee; Park, Cheolmin
This article describes our recent efforts of high throughput epitaxy of thin field-activated electroactive polymer (FEAP) films including poly(vinylidene fluoride) (PVDF), ferroelectric poly(vinylidene fluoride- co -trifluoroethylene) (PVDF-TrFE) and poly(vinylidene fluoride- co -trifluoroethylene-co-chlorofluoroethylene) (PVDF-TrFE-CTFE) for high performance organic electronic device applications. The method is based on development of highly ordered semicrystalline domains of FEAPs on a molecularly ordered poly(tetrafluoroethylene) (PTFE) substrate, combined with spin coating method over the area of a few centimetre square. In general, chain axes of FEAPs were aligned parallel to that of PTFE, i.e., the rubbing direction. More in details, the results for instance in the case of PVDF-TrFE show that the lattice match between (010)PVDF-TrFE and (100)PTFE results in b and c axis of PVDF-TrFE crystals preferentially parallel to a and c of PTFE, respectively and consequently produces global ordering of the edge-on PVDF-TrFE crystalline lamellae aligned perpendicular to the rubbing direction of PTFE, its c -axis. We also demonstrate that our epitaxially grown FEAP films on PTFE surface were successfully incorporated into various organic electronic devices for high device performance, including non-volatile memory capacitor, metal-ferroelectric-insulator-semiconductor memory element, field effect transistor type memory and high energy storage capacitor.